Method for manufacturing membrane electrode assembly and membrane electrode assembly manufactured using the method

Through the stacked structure method and drying heat treatment technology, the interlayer interface resistance and durability problems of fuel cell membrane electrode assembly are solved, and high-performance and low-cost membrane electrode assembly manufacturing is realized, simplifying the production process.

CN111370711BActive Publication Date: 2025-01-03HYUNDAI MOTOR CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201910758749.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-26
Filing Date
2019-08-16
Publication Date
2025-01-03
Estimated Expiration
2039-08-16

AI Technical Summary

Technical Problem

In the existing fuel cell membrane electrode assembly manufacturing methods, there are problems such as interface resistance, deterioration of durability, high manufacturing cost and low productivity, especially due to the incomplete transfer of resistance generated by the interlayer interface and the catalyst electrode layer, resulting in a decrease in performance and durability.

Method used

The laminated structure method is adopted, including a release film, anode layer, a porous support layer and a cathode layer, and the electrolyte film layer is formed by drying and heat treatment, reducing the interlayer interface, improving the adhesion, reducing manufacturing costs, and simplifying the manufacturing process.

Benefits of technology

The performance and durability of the membrane electrode assembly are improved, the electrode cracking and structural deformation are reduced, the manufacturing cost is reduced, the productivity is improved, and the manufacturing of ultra-thin film-type membrane electrode assembly is realized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111370711B_ABST
    Figure CN111370711B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a membrane electrode assembly and a membrane electrode assembly manufactured using the method, wherein the method for manufacturing a membrane electrode assembly comprises the following steps: forming a laminated structure, the laminated structure comprising a release film, an anode layer, a porous support layer and a cathode layer; and processing the laminated structure. The membrane electrode assembly comprises: a cathode layer; an anode layer; and an electrolyte membrane layer, the electrolyte membrane layer being arranged between the cathode layer and the anode layer, and the electrolyte membrane layer being impregnated with ionomers of the cathode layer and the anode layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing a membrane electrode assembly and a membrane electrode assembly manufactured using the method. Background Art

[0002] A fuel cell is formed by disposing separators (or bipolar plates) on both surfaces of a membrane electrode assembly (MEA), and a plurality of fuel cells may be continuously arranged to form a fuel cell stack.

[0003] Specifically, a membrane electrode assembly as a main component of a fuel cell generally has a three-layer structure, including: a polymer electrolyte layer, an anode catalyst electrode layer formed on one surface of the polymer electrolyte layer, and a cathode catalyst electrode layer formed on the opposite surface of the polymer electrolyte layer. For example, in the related prior art, a method for manufacturing a membrane electrode assembly having a three-layer structure may include a decal transfer method and a direct coating method.

[0004] Regarding the decal transfer method, a catalyst electrode layer is formed by coating a catalyst slurry on the surface of a release film and drying the catalyst slurry, a release film formed with a catalyst electrode layer is stacked on each of the two surfaces of a polymer electrolyte membrane layer, and a roller lamination process (thermal compression at high temperature and high pressure) is used to transfer and bond (laminate) the catalyst electrode layer to each of the two surfaces of the polymer electrolyte membrane layer, and the release film is removed from the catalyst electrode layer, thereby manufacturing a membrane electrode assembly with a three-layer structure. The decal transfer method may include preparing a cathode, an anode, and an electrolyte membrane layer respectively, and bonding these components to each other by thermal compression. However, the decal transfer method has the following disadvantages, for example, a large amount of auxiliary materials are used to prepare each component, and the output of various treatments is different, so the manufacturing cost is too high. In addition, resistance is generated at the interface formed between each component (cathode, anode, and electrolyte membrane layer), which may cause the performance and durability of the fuel cell to deteriorate. In addition, in order to save costs and improve performance, the thickness of the electrolyte membrane layer will be reduced, which in turn will limit the bonding of the electrode to the electrolyte membrane layer.

[0005] Meanwhile, regarding the direct coating method, the catalyst slurry is directly coated on the polymer electrolyte membrane layer and dried to form an anode, a release film (or a separate film) is removed from the opposite surface of the polymer electrolyte membrane layer, and a cathode is directly coated thereon and dried. The direct coating method includes applying the cathode and the anode directly to both surfaces of the electrolyte layer.

[0006] However, in the direct coating method, the electrolyte layer can be rapidly expanded by water and an organic solvent contained in the electrode slurry directly coated thereon. When the solvent is removed by drying, the structure of the expanded ionomer becomes dense, which can cause deformation (i.e., cracking) between the portion directly coated with the electrode slurry and the portion not coated with the electrode slurry. For example, when the electrode is coated on one surface of the electrolyte membrane layer, the release film can be removed when the other electrode is coated on the opposite surface of the electrolyte membrane layer. At this time, the electrolyte membrane layer will be greatly bent, thereby deteriorating productivity. In addition, the release film removed from the catalyst electrode layer will be pushed into a wrinkled form due to friction. At this time, a part of the catalyst electrode layer may not be completely separated from the release film, but may remain coated on the release film, so that the surface of the catalyst electrode layer transferred to the polymer electrolyte membrane layer is deformed microscopically. Thus, the durability and performance of the fuel cell using the membrane electrode assembly manufactured by the conventional manufacturing method will be deteriorated due to the incomplete transfer and surface deformation of the catalyst electrode layer.

[0007] The above information disclosed in this Background section is only for enhancement of understanding of the background of the invention and therefore the above information may contain information that does not form the prior art that is already known in this country to a person of ordinary skill in the art. Summary of the invention

[0008] A preferred aspect of the present invention provides a method for improving the performance and durability of a membrane electrode assembly by minimizing the interfaces created between layers in the membrane electrode assembly.

[0009] The present invention also provides a method, which can reduce the occurrence of electrode cracking in a membrane electrode assembly and the structural deformation of the electrode caused by removing a release film (or release paper).

[0010] In addition, the present invention provides a method that can improve productivity by reducing the number of steps, improve the performance of a fuel cell, and reduce manufacturing costs by realizing an ultra-thin film type membrane electrode assembly.

[0011] However, the objects achieved by the present invention are not limited to the above-mentioned objects. Through the following description, the objects of the present invention will become more obvious, and the objects of the present invention are achieved by using the elements and combinations thereof pointed out in the appended claims.

[0012] In one aspect, the present invention provides a method for manufacturing a membrane electrode assembly, the method comprising the steps of: forming a laminate structure, the laminate structure comprising a release film, an anode layer, a porous support layer and a cathode layer; and processing the laminate structure. The steps of forming the laminate structure include: providing a release film; forming the anode layer by coating a first electrode slurry on a first surface of the release film; stacking the porous support layer on the surface of the anode layer; and forming the cathode layer by coating a second electrode slurry on the surface of the porous support layer.

[0013] As used herein, the term "release film" refers to a material formed in a film having a thickness in the micrometer range of, for example, about 1 μm to 50 μm, and includes materials that can be partially or entirely removed or peeled off from the final product when the manufacturing process is completed. Suitable release films include, for example, materials made of or including the following materials: polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyimide (PI), polyoxymethylene (POM), polytetrafluoroethylene (PTFE), ethylene tetrafluoroethylene (EPFE), polyethylene (PE), polypropylene (PP), polycarbonate (PC), etc.

[0014] The term "anode layer" as used herein refers to a layer comprising an active anode material of a fuel cell component and having a thickness in the micrometer range of, for example, about 1 μm to 50 μm. Suitable anode layers include, for example, active anode materials made of or including a catalyst including platinum (Pt), a perfluorosulfur (PFSA)-based ionomer, and conventional additives.

[0015] The term "cathode layer" as used herein refers to a layer comprising an active cathode material of a fuel cell component and having a thickness in the micrometer range of, for example, about 1 μm to 50 μm. Suitable cathode layers include, for example, active cathode materials made of or comprising: a catalyst comprising platinum (Pt), a perfluorosulfur (PFSA)-based ionomer, and conventional additives.

[0016] As used herein, the term "porous support layer" refers to a layer that contains a porous structure (e.g., a plurality of pores) and serves as a support between stacked layers in a fuel cell assembly. The porous support layer can be formed to have a thickness in the micrometer range of, for example, about 1 μm to 50 μm. Suitable porous support layers include, for example, expanded polytetrafluoroethylene (ePTFE).

[0017] As used herein, the term "porous" refers to a structure having a plurality of pores, spaces or holes through which a solid, liquid or gas (e.g., air) can pass or be held (e.g., impregnated) in an object (e.g., a layer or matrix) through a plurality of pores, spaces or holes. In certain embodiments, the pores, porous spaces or holes may have a size ranging from nanometers, such as 1 nm to 100 nm, to micrometers, such as 1 μm to 10 μm, or preferably 1 μm to 5 μm. In certain embodiments, the pores, porous spaces or holes may be impregnated with liquids, gases or solid particles (e.g., ionomers) having a size smaller than the pore size.

[0018] The laminated structure may be heat treated. For example, the laminated structure may be treated by drying and / or heat treating. As used herein, "heat treating" refers to applying heat to a treatment area, or alternatively, to applying heat to the surroundings so as to directly apply heat and increase the temperature of the area.

[0019] Each of the anode layer and the cathode layer may include a catalyst and an ionomer. For example, the anode layer includes a first catalyst and a first ionomer, and the cathode layer includes a second catalyst and a second ionomer. The porous support layer has a porous structure including a plurality of pores, and the size of the catalyst is larger than the size of the pores in the porous support layer.

[0020] The step of stacking the porous supporting layer on the surface of the anode layer includes the step of forming the electrolyte supporting layer by impregnating the first ionomer on the surface of the anode layer in contact with the porous supporting layer into pores in the porous supporting layer.

[0021] The step of forming the cathode layer includes the following steps: forming an electrolyte membrane layer by allowing the second ionomer on the surface of the cathode layer in contact with the electrolyte supporting layer to penetrate into the pores in the electrolyte supporting layer.

[0022] The step of forming the cathode layer is performed by coating the second electrode slurry on the surface of the electrolyte supporting layer in a continuous coating manner or a pattern coating manner.

[0023] The porous support layer suitably comprises expanded polytetrafluoroethylene (ePTFE).

[0024] The laminate structure may be dried and then heat treated.

[0025] The method may further include the following step: before forming the stacked structure, providing a first electrode slurry containing a first catalyst and an ionomer.

[0026] In the first electrode slurry, the content (wt %) of the first ionomer is equal to or greater than the content (wt %) of the first catalyst.

[0027] Preferably, the content (wt %) of the first ionomer may be 1.5 times or more of the content (wt %) of the first catalyst.

[0028] The method further includes the following step: before forming the stacked structure, providing a second electrode slurry containing a second catalyst and a second ionomer.

[0029] In the second electrode slurry, the content (wt %) of the second ionomer is equal to or greater than the content (wt %) of the second catalyst.

[0030] The first ionomer of the anode layer and the second ionomer of the cathode layer include the same type of ionomer.

[0031] The size of the anode layer is larger than that of the cathode layer.

[0032] The size of the porous support layer is larger than that of the anode layer.

[0033] In another aspect, the present invention provides a membrane electrode assembly manufactured by the above method. For example, the membrane electrode assembly includes: a cathode layer; an anode layer; and an electrolyte membrane layer, the electrolyte membrane layer is arranged between the cathode layer and the anode layer, and the electrolyte membrane layer is impregnated with ionomers of the cathode layer and the anode layer.

[0034] Preferably, the thickness of the membrane electrode assembly is in the range of 10 to 50 μm.

[0035] Other aspects of the invention are discussed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The above and other features of the present invention are described in detail below with reference to certain exemplary embodiments shown in the accompanying drawings, which are given below in an exemplary manner only and therefore do not constitute a limitation of the present invention, and in which:

[0037] Figure 1 is a flow chart illustrating an exemplary method of manufacturing an exemplary membrane electrode assembly according to an exemplary embodiment of the present invention;

[0038] Figure 2 A process illustrating an exemplary method of manufacturing an exemplary membrane electrode assembly according to an exemplary embodiment of the present invention;

[0039] Figure 3 is a flow chart illustrating an exemplary method of manufacturing an exemplary membrane electrode assembly according to an exemplary embodiment of the present invention;

[0040] Figure 4 A process illustrating an exemplary method of manufacturing an exemplary membrane electrode assembly according to an exemplary embodiment of the present invention;

[0041] Figure 5is a view showing an exemplary apparatus for manufacturing a membrane electrode assembly according to an embodiment of the present invention; and

[0042] Fig. 6A and Figure 6B The electrodes in the membrane electrode assembly manufactured according to the decal transfer method in the related art are shown.

[0043] It should be understood that the accompanying drawings are not necessarily drawn to scale, presenting a somewhat simplified representation of various preferred features illustrating the basic principles of the invention. The specific design features of the present invention as disclosed herein, including, for example, specific dimensions, orientations, locations, and shapes will be determined in part by the specific intended application and use environment.

[0044] In the drawings, reference numbers refer to the same or equivalent parts of the present invention throughout the several figures of the drawings. DETAILED DESCRIPTION

[0045] Hereinafter, exemplary embodiments of the present invention will be described in detail with reference to the accompanying drawings. Advantages and features of the present invention and methods for achieving the advantages and features will be clarified from the embodiments described in detail below with reference to the accompanying drawings. However, the present invention can be embodied in many different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that the present invention is thorough and complete, and the scope of the present invention is fully conveyed to those skilled in the art. The present invention is limited only by the scope of the claims. Throughout the specification, similar reference numerals refer to similar components.

[0046] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. It will also be understood that terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and will not be interpreted in an ideal or overly formal sense unless clearly defined in this specification.

[0047] The terms used herein are only used for the purpose of describing specific embodiments and are not intended to limit the present invention. Unless the context clearly indicates, the singular forms "one", "an" and "the" as used herein are intended to also include plural forms. It should also be understood that when using terms such as "including" and / or "comprising" in this specification, it is intended to illustrate the presence of the feature, integer, step, operation, element and / or component, without excluding the presence or increase of one or more other features, integers, steps, operations, elements, components, and / or their combinations. As used herein, the term "and / or" includes any and all combinations of one or more related listed items.

[0048] It should be understood that when an element such as a layer, film, region, or panel is referred to as being "on another element," the element may be directly on the other element or intervening elements may be present. It should be understood that when an element such as a layer, film, region, or panel is referred to as being "under another element," the element may be directly under the other element or intervening elements may be present.

[0049] Unless otherwise specified, all numbers, values ​​and / or expressions used herein relating to quantities of ingredients, reaction conditions, polymer compositions and formulations will be understood to be modified in all instances by the term "about", since such numbers themselves are approximate, reflecting, among other things, the various measurement uncertainties encountered in obtaining such values. For example, "about" may be understood to be within 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.1%, 0.05% or 0.01% of the stated value.

[0050] In addition, in the case of numerical ranges disclosed herein, such ranges are continuous and, unless otherwise specified, include every value from the minimum value to the maximum value of such ranges and including the maximum value of such ranges. In addition, in the case of such ranges referring to integers, unless otherwise specified, include every integer from the minimum value to the maximum value and including the maximum value.

[0051] In the context of this specification, where a range is specified for a parameter, it should be understood that the parameter includes all values ​​within the specified range, including the endpoints of the specified range. For example, a range of "5 to 10" will be understood to include the values ​​5, 6, 7, 8, 9 and 10, as well as any sub-ranges within the specified range, such as sub-ranges including 6 to 10, 7 to 10, 6 to 9, 7 to 9, etc., and includes any values ​​and ranges between reasonable integers in the context of the specified range, such as 5.5, 6.5, 7.5, 5.5 to 8.5 and 6.5 to 9, etc. For example, a range of "10% to 30%" will be understood to include the values ​​10%, 11%, 12%, 13%, and all integers up to and including 30%, as well as any sub-ranges within the specified range, such as sub-ranges including 10% to 15%, 12% to 18%, 20% to 30%, etc., and including any values ​​and ranges between integers that are reasonable in the context of the specified range, such as 10.5%, 15.5%, 25.5%, etc.

[0052] Hereinafter, exemplary embodiments of the present invention will be described in detail with reference to the accompanying drawings.

[0053] Figure 1 is a flow chart illustrating an exemplary method of manufacturing an exemplary membrane electrode assembly (MEA) according to an exemplary embodiment of the present invention, Figure 2A process of an exemplary method of manufacturing a membrane electrode assembly according to an exemplary embodiment of the present invention is shown.

[0054] The method for manufacturing a membrane electrode assembly according to an exemplary embodiment of the present invention may include steps of forming a stacked structure (S10 to S40), and a step of treating (e.g., drying and heat treating) the stacked structure (S50). For example, the step of forming the stacked structure may include a step of preparing a release film (S10), a step of forming an anode layer by coating a first electrode slurry on a first surface of the release film (S20), a step of stacking a porous support layer on the surface of the anode layer (S30), and a step of forming a cathode layer by coating a second electrode slurry on the surface of the porous support layer (S40).

[0055] Unlike a conventional membrane electrode assembly manufacturing method using at least three release films, in steps S10 to S40 of forming a stacked structure according to an exemplary embodiment of the present invention, a release film may not be used in each of steps S10 to S40, but only a single release film may be used in step S10 to form the stacked structure. Therefore, the manufacturing process can be simplified, the amount of auxiliary materials used in the manufacturing process can be reduced, and the manufacturing process can be continuously performed.

[0056] In addition, in the related prior art, because the processes of forming each layer have different yields from each other, the productivity of the membrane electrode assembly manufactured using the layers is low. However, according to various exemplary embodiments of the present invention, the membrane electrode assembly manufacturing method includes fewer processes and thus exhibits superior productivity.

[0057] The step S40 of forming the cathode layer can be performed by coating the second electrode slurry on the porous support layer in a continuous coating manner or a pattern coating manner, but is not limited thereto. Any of various other coating methods can be used.

[0058] Specifically, the method may include drying to remove the solvent after the steps S10 to S40 of forming the stacked structure. In the related prior art, a conventional membrane electrode assembly manufacturing method (e.g., a decal transfer method) includes a drying process performed in the middle of the step of forming the stacked structure. Preferably, the drying process (S50) may be performed after forming the stacked structure (S20 to S40).

[0059] Therefore, the bonding process (i.e., coating or stacking) may not be hindered by the shrinkage or expansion of the ionomer contained in each layer. For example, in steps S20 to S40 of forming each layer, since the layers are already in a wet state, the ionomer contained in each layer may be in an expanded state, and therefore, the layers may be packaged (or stacked) without generating interface resistance. In contrast, in conventional membrane electrode assembly manufacturing methods, the ionomers dispersed in each layer are in a state of expansion in a bulky form and are entangled in a complex chain form when dried. Therefore, when the ionomer is repeatedly wetted and dried according to an exemplary embodiment, fine spaces are generated in the interfaces between the layers, thereby increasing the interface resistance.

[0060] Therefore, when each layer is dried independently according to a conventional method, the structure of each layer is deformed, a fine space is formed between the layers, and an interface resistance may be generated, thereby deteriorating the performance and durability of the membrane electrode assembly. However, according to various exemplary embodiments of the present invention, since the laminated structure is dried once without performing drying in each layer forming step, the structural deformation of each layer and the resistance in the thickness direction thereof (i.e., the interface resistance) are reduced, thereby improving the performance and durability of the membrane electrode assembly, and thus a thin film or ultra-thin film membrane electrode assembly can be obtained. In addition, the amount of auxiliary materials used in each process can be reduced, and the number of drying steps can be reduced, thereby improving productivity.

[0061] In particular, the conventional direct coating method (or multilayer coating method) in the related prior art has a problem in that the layers are likely to crack or wrinkle due to the shrinkage and expansion of the layers, but the membrane electrode assembly manufacturing method according to various exemplary embodiments of the present invention can substantially reduce the generation of cracks or wrinkles. For example, since the electrode structure (S20 and S40) formed by coating the electrode slurry in a fluid state is dried together, the electrode structure can shrink and expand uniformly, thereby reducing the generation of cracks or wrinkles. Therefore, the quality, performance and durability of the membrane electrode assembly can be improved.

[0062] Meanwhile, according to the membrane electrode assembly manufacturing method of the exemplary embodiment of the present invention, in the step S50 of drying and heat-treating the laminated structure, the laminated structure may be heat-treated after the drying treatment. However, the present invention is not limited thereto. Alternatively, the laminated structure may be dried and heat-treated at the same time. The heat treatment step may allow the layers of the laminated structure to be fully bonded to each other.

[0063] In the following, reference Figure 2 The steps of a method of manufacturing a membrane electrode assembly according to an exemplary embodiment of the present invention are described in detail.

[0064] like Figure 2 As shown, in the step of forming a stacked structure according to an exemplary embodiment of the present invention (referring to Figure 1In S10 to S40 in the above, each of the anode layer 220 and the cathode layer 240 may include a catalyst 201 and an ionomer 205, and the porous support layer 300 may have a porous structure in which a plurality of pores may be formed. For example, the anode layer may include a first catalyst and a first ionomer, and the cathode layer may include a second catalyst and a second ionomer. The size of the catalyst 201 (e.g., the first catalyst and the second catalyst) may be larger than the size of the pores in the porous support layer 300.

[0065] After step S20 of forming the anode layer 220 on one surface of the release film 100, in step S30 of stacking the porous supporting layer 300 on the surface of the anode layer 220, the ionomer 205 on the surface of the anode layer 220 in contact with the porous supporting layer 300 may be impregnated into the pores in the porous supporting layer 300. Specifically, since the porous supporting layer 300 is disposed on the anode layer 220, a portion of the ionomer 205 of the anode layer 220 may be absorbed into the pores of the porous supporting layer 300 under the action of capillary phenomenon. In this way, the ionomer 205 of the anode layer 220 may be impregnated, for example, the first ionomer of the anode layer 220 may be impregnated. Therefore, the electrolyte supporting layer 310 may be formed, and a portion of the ionomer 205 of the anode layer 220 is impregnated into the electrolyte supporting layer 310.

[0066] The release film 100 may include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyimide (PI), polyoxymethylene (POM), polytetrafluoroethylene (PTFE), ethylene tetrafluoroethylene (ETFE), polyethylene (PE), polypropylene (PP), polycarbonate (PC), or a combination thereof.

[0067] Meanwhile, since the size of the catalyst 201 contained in the anode layer 220 is larger than the size of the pores of the porous supporting layer 300 , the catalyst 201 cannot move from the anode layer 220 into the porous supporting layer 300 .

[0068] In step S40 of forming cathode layer 240, ionomer 205 on the surface of cathode layer 240 in contact with electrolyte supporting layer 310 penetrates into the pores of electrolyte supporting layer 310. Specifically, a portion of ionomer 205 of cathode layer 240 is absorbed into the pores of electrolyte supporting layer 310 by surface tension, so that ionomer 205 of cathode layer 240 is penetrated, for example, second ionomer is penetrated. Therefore, electrolyte membrane layer 320 can be formed, and a portion of ionomer 205 of cathode layer 240 penetrates into electrolyte membrane layer 320. As described above, step S40 of forming cathode layer is performed by coating the second electrode slurry on electrolyte supporting layer 310 in a continuous coating manner or a pattern coating manner, for example.

[0069] A portion of the ionomer 205 that does not penetrate into the electrolyte supporting layer 310 but is left behind may be used as an ionomer of an electrode between the cathode layer 240 and the electrolyte membrane layer 320. In addition, since the size of the catalyst 201 contained in the cathode layer 240 is larger than the size of the pores in the electrolyte supporting layer 310, the catalyst 201 cannot move from the cathode layer 240 to the electrolyte supporting layer 310, but only the ionomer 205 may selectively penetrate into the electrolyte supporting layer 310.

[0070] Specifically, the ionomer 205 that permeates into the electrolyte supporting layer 310 to form the electrolyte membrane layer 320 in the step S40 of forming the cathode layer 240 may be in contact with the ionomer 205 impregnated into the electrolyte supporting layer 310 formed in the step S30 of stacking the porous supporting layer 300 on the surface of the anode layer 220. Therefore, the pores in the porous supporting layer 300 may be filled with the ionomer 205 derived from each of the anode layer 220 and the cathode layer 240, thereby forming the electrolyte membrane layer 320 impregnated with the ionomer 205.

[0071] Meanwhile, the porous supporting layer 300 according to an exemplary embodiment of the present invention may include expanded polytetrafluoroethylene (ePTFE). Figure 1 The electrolyte membrane layer 320 in the laminated structure prepared by the steps S10 to S40 in the above method may include expanded polytetrafluoroethylene (ePTFE), thereby increasing the tensile strength of the membrane electrode assembly and preventing changes in its size.

[0072] Meanwhile, in order to improve the durability of the fuel cell, the porous supporting layer 300 , the electrolyte supporting layer 310 , or the electrolyte membrane layer 320 may not exclude materials other than expanded polytetrafluoroethylene (ePTFE).

[0073] Figure 3 is a flow chart showing a method for manufacturing a membrane electrode assembly (MEA) according to another exemplary embodiment of the present invention, Figure 4 The process of an exemplary method for manufacturing an exemplary membrane electrode assembly according to another exemplary embodiment of the present invention is shown. For ease of description, the following description will focus on the reference Figure 1 and Figure 2 Differences in the embodiments described.

[0074] like Figure 3As shown, the method also includes, before steps S10 to S40 of forming a laminated structure according to another embodiment of the present invention, a step (S2) of preparing an electrode slurry by mixing and dispersing a catalyst and an ionomer. The step S2 of preparing the electrode slurry may include the step of preparing a first electrode slurry. Alternatively, in other embodiments of the present invention, the step S2 of preparing the electrode slurry may include the step of preparing a first electrode slurry and the step of preparing a second electrode slurry. However, the present invention is not limited thereto. For example, before forming the laminated structure (S10 to S40), a first electrode slurry (S20) may be prepared by mixing and dispersing a first catalyst and a first ionomer, and a porous support layer may be stacked on the surface of the anode layer (S30). Subsequently, a second electrode slurry prepared by mixing and dispersing a second catalyst and a second ionomer is coated on the electrolyte support layer to form a cathode layer (S40).

[0075] Unlike conventional membrane electrode assembly manufacturing methods (e.g., decal transfer method or direct coating method) in which the formation of layers requires at least three solvent dispersion processes (the at least three solvent dispersion processes include dispersion of electrode slurry to form a cathode layer, dispersion of electrode slurry to form an anode layer, and dispersion of ionomer to form an electrolyte membrane layer), the membrane electrode assembly can be manufactured by two solvent dispersion processes (e.g., preparation of a first electrode slurry and preparation of a second electrode slurry). Therefore, the number of steps can be reduced, thereby improving productivity. In addition, the amount of auxiliary materials used in each step can be reduced, thereby reducing manufacturing costs.

[0076] like Figure 4 As shown, according to another exemplary embodiment of the present invention, the method for manufacturing a membrane electrode assembly may further include a step of preparing an electrode slurry by mixing and dispersing a catalyst 201 (e.g., a first catalyst) and an ionomer 205 before forming an anode layer 220 on the first surface of the prepared release film 100 (e.g., the first catalyst, as in Figure 3 is referred to as S2).

[0077] Preferably, the first electrode slurry includes a content (wt%) of the first ionomer 205 that is equal to or greater than the content (wt%) of the first catalyst 201. For example, the anode layer 220 may be formed so that a larger amount of the ionomer 205 is included in the first electrode slurry than the catalyst 201. Preferably, the content (wt%) of the ionomer 205 (e.g., the first ionomer) may be 1.5 times or more of the content (wt%) of the catalyst 201 (e.g., the first catalyst).

[0078] Specifically, the first electrode slurry includes the first catalyst in an amount of 20 wt % to 50 wt %, preferably 40 wt % to 50 wt %, and the first ionomer in an amount of 50 wt % to 80 wt %, preferably 50 wt % to 60 wt %.

[0079] As described above, in other embodiments of the present invention, before the step of forming the stacked structure (S10 to S40), a step of preparing a second electrode slurry by mixing and dispersing the catalyst 201 (eg, the second catalyst) and the ionomer 205 (eg, the second ionomer) may be performed.

[0080] In the second electrode slurry, the content (wt%) of the ionomer 205 (e.g., the second ionomer) may be equal to or greater than the content (wt%) of the catalyst 201 (e.g., the second catalyst). Preferably, in the second electrode slurry, the ratio of the content (molar) of the ionomer 205 (e.g., the second ionomer) to the content (molar) of the catalyst 201 (e.g., the second catalyst) may be approximately 1:1, or a larger amount of the ionomer 205 (e.g., the second ionomer) may be included compared to the catalyst 201 (e.g., the second catalyst).

[0081] Specifically, the second electrode slurry includes the second catalyst in an amount of 20 wt % to 50 wt %, preferably 40 wt % to 50 wt %, and the second ionomer in an amount of 50 wt % to 80 wt %, preferably 50 wt % to 60 wt %.

[0082] Figure 5 An exemplary apparatus for manufacturing a membrane electrode assembly according to an exemplary embodiment of the present invention is shown.

[0083] like Figure 5 As described above, the laminated structure can be formed by using the membrane electrode assembly manufacturing method according to various exemplary embodiments of the present invention, that is, by performing the following steps: forming the anode layer 220 ( Figure 1 S10 and S20 in the above), by stacking a porous support layer 300 (e.g., ePTFE) on the surface of the anode layer 220 ( Figure 1 S30 in the electrolyte support layer ( Figure 4 310 in the electrolyte support layer 310), and by coating a second electrode slurry ( Figure 4 320) forms a cathode layer 240 and an electrolyte membrane layer (referring to Figure 1 Then, the stacked structure may be moved to a drying oven 50 so that it is dried while passing through the drying oven 50 ( Figure 1 In addition, during the drying process, heat treatment may also be performed to solidify the adhesion between the layers 220, 240 and 320 (S50).

[0084] Therefore, the stacked structures 220, 240, and 320 (S10) can be formed using a smaller amount of release film 100 without using a release film in each step of S10 to S40. Therefore, the manufacturing process can be simplified and the amount of auxiliary materials used in each process can be reduced.

[0085] In addition, if Figure 5 As shown, since it is not necessary to separately prepare the respective layers 220, 240, and 320 and bond the layers to each other, the manufacturing process of the membrane electrode assembly can be continuously performed.

[0086] The membrane electrode assembly manufactured according to various exemplary embodiments of the present invention includes an anode layer 220 , a cathode layer 240 , and an electrolyte membrane layer 320 interposed between the anode layer 220 and the cathode layer 240 .

[0087] Anode layer 220 can be formed using a first electrode slurry. Anode layer 220 includes a first catalyst, a first ionomer, and conventional additives such as an antioxidant. The first catalyst includes a carbon-supported Pt catalyst (Pt / C). The first ionomer includes an ionomer based on PFSA. Anode layer 220 includes a first catalyst in an amount of 20wt% to 50wt%, a first ionomer in an amount of 50wt% to 80wt%, and a small amount of additives. Since anode layer 220 includes a first catalyst greater than 20wt%, anode layer 220 has electrical conductivity. Anode layer 220 decomposes hydrogen supplied from the outside into protons and electrons.

[0088] The cathode layer 240 can be formed using a second electrode slurry. The cathode layer 240 includes a second catalyst, a second ionomer, and conventional additives such as an antioxidant. The second catalyst includes a carbon-supported Pt catalyst (Pt / C). The second ionomer includes a PFSA-based ionomer. The cathode layer 240 includes a second catalyst in an amount of 20wt% to 50wt%, a second ionomer in an amount of 50wt% to 80wt%, and a small amount of additives. Since the cathode layer 240 includes more than 20wt% of the second catalyst, the cathode layer 240 has conductivity. The cathode layer 240 reacts oxygen supplied from the outside with protons transported from the anode layer 220 to produce water.

[0089] The electrolyte membrane layer 320 is electrically insulating and moves protons generated by the anode layer 220 to the cathode layer 240 .

[0090] In the membrane electrode assembly manufactured according to an embodiment of the present invention, the anode layer 220 and the cathode layer 240 may include the same type of ionomer, for example, the first ionomer and the second ionomer may be the same type of ionomer. Therefore, the electrolyte membrane layer 320 may include the same type of ionomer as the ionomer of the anode layer 220 and the cathode layer 240. However, in order to improve the performance of the membrane electrode assembly, it is not excluded to include other types of ionomers.

[0091] In addition, if Figure 5 As shown, in the membrane electrode assembly manufactured according to various exemplary embodiments of the present invention, the anode layer 220 may be larger than the cathode layer 240, for example, the planar area of ​​the anode layer may be larger than the planar area of ​​the cathode layer. The porous support layer 300 (e.g., ePTFE) may be larger than the anode layer 220, for example, the planar area of ​​the porous support layer may be larger than the planar area of ​​the anode layer. In other words, the relatively cheap and easily available porous support layer 300 (e.g., ePTFE) can be formed to have a maximum area (planar area), and the anode layer 220 and the cathode layer 240 containing precious metals (e.g., platinum (Pt)) or rare earth elements can be formed to be smaller. In addition, by forming the cathode layer 240 to be smaller than the anode layer 220, the amount of precious metals (e.g., platinum (Pt)) used is further reduced, thereby reducing the cost of manufacturing the membrane electrode assembly.

[0092] In addition, as described above, in the membrane electrode assembly manufactured according to the exemplary embodiment of the present invention, the membrane electrode assembly has a total thickness in the range of about 10 μm to 50 μm due to the minimum interface generated between the layers 220, 240 and 320. In addition, a thin film type or ultra-thin film type membrane electrode assembly having a total thickness of about 15 μm or less, specifically, in the range of about 10 to 15 μm, can be manufactured.

[0093] Fig. 6A and Figure 6B is a view showing electrodes in a membrane electrode assembly manufactured according to a conventional decal transfer method.

[0094] Fig. 6A FIG. 4 shows the surface of the electrolyte membrane layer before coating the electrode layer (anode layer or cathode layer) according to the decal transfer method. Fig. 6A , surfaces of electrolyte membrane layers having thicknesses of 10 μm, 15 μm, and 20 μm, respectively, are sequentially shown from the left.

[0095] Figure 6B The electrode layer is transferred to the Fig. 6A The results for each of the surfaces of the electrolyte membrane layers are shown in FIG. Fig. 6AIt can be confirmed that an electrode non-transfer area (e.g., a light-colored portion) is produced. In particular, in an experiment in which the electrode was heat-compressed onto the surface of an electrolyte membrane layer having a thickness of 10 μm, most of the electrodes were not bonded to the electrolyte membrane layer. In an experiment in which the electrode was heat-compressed onto the surface of an electrolyte membrane layer having a thickness of 15 μm, most of the electrodes were not bonded to the electrolyte membrane layer, but the transfer of the electrode was slightly improved compared to transferring the electrode to an electrolyte membrane layer having a thickness of 10 μm. Therefore, when the electrode is heat-compressed onto the surface of an electrolyte membrane layer having a thickness of 20 μm or more, most of the electrodes are bonded to the electrolyte membrane layer without producing a non-transfer area. Therefore, the decal transfer method cannot manufacture a membrane electrode assembly having a thickness of less than 20 μm. However, according to the membrane electrode assembly manufacturing method of various exemplary embodiments of the present invention, a membrane electrode assembly having a thickness of less than about 15 μm, preferably less than about 10 μm, can be manufactured while ensuring the performance of the membrane electrode assembly. Therefore, a thin film or ultra-thin film membrane electrode assembly can be manufactured.

[0096] Therefore, in the conventional decal method, when each layer is dried independently, the structure of each layer is deformed, a fine space is formed between the layers, and an interface resistance is generated. In contrast, according to various exemplary manufacturing methods of the present invention, since the entire laminated structure is dried without performing a drying step at each layer forming step, the structural deformation of each layer and the resistance in the thickness direction thereof (e.g., interface resistance) are reduced, thereby manufacturing a firmly bonded membrane electrode assembly. The membrane electrode assembly manufactured in this manner can have improved performance and durability. In addition, the number of drying steps can be reduced, thereby improving productivity. In addition, the amount of auxiliary materials used in each process can be reduced, thereby achieving an economic effect, that is, a reduction in manufacturing costs.

[0097] Therefore, interfaces generated between layers in the membrane electrode assembly can be minimized and a large amount of ionomer contained in the anode layer can be impregnated into the electrolyte layer, thereby improving the performance and durability of the fuel cell, thereby realizing an ultra-thin membrane type membrane electrode assembly.

[0098] Furthermore, cracks generated in electrodes in a membrane electrode assembly may be reduced, manufacturing costs may be reduced by minimizing the amount of release films used in a manufacturing process, and structural deformation of electrodes caused when removing the release films may be reduced.

[0099] Furthermore, improvement in productivity and energy saving can be achieved through reduction in the number of steps and reduction in manufacturing cost, and improvement in performance of a fuel cell can be achieved through realization of an ultra-thin membrane type membrane electrode assembly.

[0100] Those skilled in the art should appreciate that the effects achievable by the present invention are not limited to those that have been specifically described above, and other effects of the present invention will be more clearly understood from the above detailed description.

[0101] The present invention has been described in detail with reference to various exemplary embodiments of the present invention. However, it should be appreciated by those skilled in the art that changes may be made in these embodiments of the present invention without departing from the principles and spirit of the present invention, and the protection scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for manufacturing a membrane electrode assembly, comprising the following steps: forming a laminated structure, the laminated structure comprising a release film, an anode layer, a porous support layer and a cathode layer; as well as processing the laminate structure, Wherein, the step of forming the stacked structure comprises the following steps: (i) providing the release film; (ii) forming the anode layer by coating a first electrode slurry on the first surface of the release film; (iii) stacking the porous support layer on the surface of the anode layer; and (iv) forming the cathode layer by coating a second electrode slurry on the surface of the porous support layer, The laminated structure is dried after the step of forming the laminated structure, and the laminated structure is formed without drying in steps (ii) and (iv).

2. The method according to claim 1, wherein: The laminate structure is processed by drying and heat treatment.

3. The method according to claim 1, wherein: The anode layer includes a first catalyst and a first ionomer, and the cathode layer includes a second catalyst and a second ionomer, wherein the porous supporting layer has a porous structure comprising a plurality of pores, and The size of the first catalyst or the second catalyst is larger than the size of the pores in the porous supporting layer.

4. The method according to claim 3, wherein: The step of stacking the porous supporting layer on the surface of the anode layer comprises the step of forming an electrolyte supporting layer by impregnating the first ionomer on the surface of the anode layer in contact with the porous supporting layer into pores in the porous supporting layer.

5. The method according to claim 4, wherein: The step of forming the cathode layer includes the step of forming an electrolyte membrane layer by allowing the second ionomer on the surface of the cathode layer in contact with the electrolyte supporting layer to penetrate into the pores in the electrolyte supporting layer.

6. The method according to claim 5, wherein: The step of forming the cathode layer is performed by coating the second electrode slurry on the surface of the electrolyte supporting layer in a continuous coating manner or a pattern coating manner.

7. The method according to claim 1, wherein: The porous support layer includes expanded polytetrafluoroethylene (ePTFE).

8. The method according to claim 2, wherein: In the step of treating the laminated structure, the laminated structure is dried and then heat-treated.

9. The method according to claim 1, further comprising the steps of: Before forming the stacked structure, a first electrode slurry including the first catalyst and an ionomer is provided.

10. The method according to claim 9, wherein: The first electrode slurry is prepared by mixing the catalyst and the ionomer.

11. The method according to claim 10, wherein: In the first electrode slurry, the content (wt %) of the ionomer is equal to or greater than the content (wt %) of the first catalyst.

12. The method according to claim 9, further comprising the steps of: Prior to forming the stacked structure, a second electrode slurry comprising a second catalyst and a second ionomer is provided.

13. The method according to claim 12, wherein: The second electrode slurry is prepared by mixing the second catalyst and the second ionomer.

14. The method according to claim 12, wherein: In the second electrode slurry, the content (wt %) of the ionomer is equal to or greater than the content (wt %) of the second catalyst.

15. The method according to claim 12, wherein: The first ionomer of the anode layer and the second ionomer of the cathode layer include the same type of ionomer.

16. The method according to claim 9, wherein: The size of the anode layer is greater than that of the cathode layer.

17. The method according to claim 12, wherein: The size of the porous support layer is larger than that of the anode layer.

18. A membrane electrode assembly manufactured using the method according to claim 1, comprising: cathode layer; Anode layer; as well as An electrolyte membrane layer is disposed between the cathode layer and the anode layer, and the electrolyte membrane layer is impregnated with ionomers of the cathode layer and the anode layer.

19. The membrane electrode assembly according to claim 18, wherein: The thickness of the membrane electrode assembly is in the range of 10 to 50 μm.